Defining metaniches in the oral cavity according to their microbial composition and cytokine profile - Seidel, Corinna Lesley; Gerlach, Roman; Wiedemann, Patrick; Weider, Matthias; Rodrian, Gabriele; Hader, Michael; Frey, Benjamin; Gaipl, Udo; Bozec, Aline; Cieplik, Fabian; Kirschneck, Christian; Bogdan, Christian; et al. (International Journal of Molecular Sciences, 2020)
The human oral microbiota consists of over 700 widespread taxa colonizing the oral cavity in several anatomically diverse oral niches. Lately, sequencing of the 16S rRNA genes has become an acknowledged, culture-independent method to characterize the oral microbiota. However, only a small amount of data are available concerning microbial differences between oral niches in periodontal health and disease. In the context of periodontitis, the cytokine expression in the gingival crevicular fluid has been studied in detail, whereas little is known about the cytokine profile in hard and soft tissue biofilms. In order to characterize oral niches in periodontal health, the oral microbiota and cytokine pattern were analyzed at seven different sites (plaque (P), gingival crevicular fluid (GCF), saliva (S), tongue (T), hard palate (HP), cheek (C) and sublingual area (U)) of 20 young adults using next-generation sequencing and multiplex immunoassays. Site-specific microbial compositions were detected, which clustered into three distinct metaniches (“P-GCF”, “S-T-HP” and “C-U”) and were associated with niche-/metaniche-specific cytokine profiles. Our findings allow the definition of distinct metaniches according to their microbial composition, partly reflected by their cytokine profile, and provide new insights into microenvironmental similarities between anatomical diverse oral niches.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cytokine profile; Metaniches; Multiplex immunoassay; Next-generation sequencing; Oral biofilms and fluids; Oral microbiota; Oral niches